Using hydrotherapy at different temperatures for promoting recovery in professional athletes - Slaga, J.; Gizinska, M.; Rutkowski, R.; Raglewska, P.; Balkó, Š.; Straburzynska-Lupa, A. (Trends in Sport Sciences, 2018)
The authors discuss possible uses of hydrotherapy in promoting recovery in professional athletes and provide an overview of literature presenting its current application in sports, whilst emphasizing the need for further research. Understanding the mechanism of action of water used at different temperatures on post-exercise recovery and examining the effectiveness of hydrotherapy methods in athletes will enable the development of optimal treatment regimens